Synthesis of aminoanthraquinone derivatives from quinizarin - Juhan, Siti Fadilah (2013)
Amino derivatives of anthraquinone have been known to have a wide range of reactivities as anticancer agents, where modifications such as reduction, alkylation, or acylation to the anthraquinones also play important roles to increase their bioactivities. Twelve aminoanthraquinones including eight new aminoanthraquinones were synthesized via two different routes that consisted of two-step reactions. In the first route, quinizarin (6) was subjected to reduction, alkylation and acylation separately, thus giving an intermediate of 4-hydroxyanthracene-1,10-dione (82), 1-hydroxy-4-methoxyanthracenedione (49) and 4-hydroxy-9,10-dioxo-9,10-dihydroanthracene-1-yl acetate (84) before further reacting to produce anthracene-1,4-dione (83), 1,4-dimethoxyanthracene-9,10-dione (50) and 9,10-dioxo-9,10-dihydroanthracene-1,4-diyl diacetate (85) in excellent yields. These three products were then treated with butyamine (BuNH2) in the presence of iodobenzene-diacetate (PhI(OAc)2) as a catalyst to produce aminoanthraquinones 2-(butylamino)anthracene-1,4-dione (83a), 2-(butylamino)-4-methoxyanthracene-9,10-dione(50a),2,3(dibutylamino)anthracene-9,10-dione (50b), 1-(butylamino)-4-methoxyanthacene-9,10-dione (50c), 1,4-(dibutylamino)anthracene-9,10-dione (50d) and 2-(butylamino)-1,4-dihydroxyanthracene-9,10-dione (86). In the second route, compound 6 first underwent amination to give 2-(butylamino)-1,4-dihydroxyanthracene-9,10-dione (86) (major product) and 1-(butylamino)-4-hydroxyanthracene-9,10-dione (87, minor product). Compound 86 was then subjected to reduction, alkylation and acylation separately. Reduction of compound 86 resulted in the compound 83a which is the same compound produced in the first route whereas methylation gave a mixture of 2-(butyamino)-1-hydroxy 4-methoxyanthracene-9,10-dione (86a) and 2-(butyamino)-1,4-dimethoxyanthracene-9,10-dione (86b). The acylation produced a mixture of 3-(butylamino)-4-hydroxy-9,10-dioxo-9,10 dihydroanthracene-1-yl acetate (86c), 2-(butylamino)-4-hydroxy-9,10-dioxo-9,10-dihydroanthracene-1-yl acetate (86d) and 2-(butylamino)-9,10-dioxo-9,10-dihydroanthracene-1,4-diyl diacetate (86e). The products were characterised via a variety of physico-chemical and spectroscopic techniques, including melting point measurements, Fourier Transform Infrared Spectroscopy (FT-IR), Direct Injection Mass Spectrometry (DI-MS), Gas Chromatography Mass Spectrometry (GCMS) and also Nuclear Magnetic Resonance spectroscopy (NMR). Compound 86e exhibited strong antimicrobial activities toward Methicillin-resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa, Candida albicans and Escherichia coli (MIC values of 0.1 - 0.5 mg/mL). Meanwhile, compounds 83a, 50a, 50c, 86a, 86b and 86e showed strong activities against both human estrogen receptor positive breast cancer (MCF-7) (IC50 1.1 - 11.0 μg/mL) and human hepatocarcinoma (Hep-G2) (IC50 1.1 - 14.0 μg/mL) cell lines.